2013
DOI: 10.1200/jco.2013.31.4_suppl.578
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of regorafenib for pretreated metastatic colorectal cancer patients in the United States.

Abstract: 578 Background: There is an unmet need for treatments that provide a survival benefit for patients with heavily pretreated metastatic colorectal cancer (mCRC). In a randomized, double-blind, placebo-controlled trial, patients treated with regorafenib plus best supportive care (BSC) had significant improvement in overall survival (OS) versus patients in the placebo arm receiving BSC alone. The aim of this study was to estimate the cost-effectiveness of regorafenib for the treatment of patients with mCRC after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Their analysis showed that patients treated with regorafenib had improved OS in comparison with those on BSC alone (0.75 versus 0.60 years), but regorafenib treatment was also associated with higher lifetime costs than BSC alone ($97,700 versus $59,494). 36 Gold-stein et al also studied the cost-effectiveness of regorafenib in the third-line setting for mCRC patients, using a Markov model. 37 Treatment with regorafenib provided an additional 0.13 life-years at a cost of $40,000, resulting in an incremental cost-effectiveness ratio of $900,000 per quality-adjusted life-years.…”
Section: Special Considerations Regarding Regorafenib Usementioning
confidence: 99%
“…Their analysis showed that patients treated with regorafenib had improved OS in comparison with those on BSC alone (0.75 versus 0.60 years), but regorafenib treatment was also associated with higher lifetime costs than BSC alone ($97,700 versus $59,494). 36 Gold-stein et al also studied the cost-effectiveness of regorafenib in the third-line setting for mCRC patients, using a Markov model. 37 Treatment with regorafenib provided an additional 0.13 life-years at a cost of $40,000, resulting in an incremental cost-effectiveness ratio of $900,000 per quality-adjusted life-years.…”
Section: Special Considerations Regarding Regorafenib Usementioning
confidence: 99%
“…The model was also previously described in 2 posters. 20,21 The model structure is shown in see Appendix Figure 1 in Supplemental Materials found at https://doi.org/10.1016/j.jval.2019.06.010.…”
Section: Ce Modelmentioning
confidence: 99%